IEEE 802.15.4 differentiated service strategy based on reinforcement-learning - Liang QIAN; Zhi-hong QIAN; Tian-ping LI; Wei QUAN (Tongxin xuebao)
To provide better support in differentiated service for IEEE 802.15.4,a novel differentiated service mechanism was proposed based on BCS(back off counter scheme)and reinforcement learning.In terms of end-device,BCS backoff strategy was added to original priority-based differentiated strategy to solve the service differentiation problem under higher traffic condition.Whil “ e for the coordinator,a reinforcement learning based duty-cycle adjustment algorithm was proposed toself-learning”an optimal duty-cycle according to different application requirements and environmental changes.Simulation shows that the proposed algorithm can meet the performance requirements of high-priority service under different environments and adjust the duty-cycle when traffic is changed,which showed a strong environmental adaptability.